MENUMBUHKAN MINAT GENERASI MUDA UNTUK MEMPELAJARI MUSIK TRADISIONAL - Abid, Mas'ud (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
Traditional music is a music that lives in the community for generation to generation, then maintained as a means of entertainment. But with the development of technology today, traditional music is very difficult to get a place in the hearts of listeners. The young generation who are supposed to defend traditional music now feels that traditional music is their unattractive musical tastes such as western music which is very interestingly presented in terms of composition and presentation so that they assume that traditional music is outdated music. This study aims to find out what is the reason for the younger generation to be less interested in learning traditional music and finding solutions so that the younger generation is interested in learning and preserving traditional music. The research method used is qualitative research.The results of the study show that there needs to be an active role of educators in introducing traditional music to the next generation.